Kesalahan Struktur Kalimat dalam Teks Berita pada Website IDN.Times Edisi Bulan September 2025 - Yasmina Zalfa; M. Daffa’ Amri; Amanda Arinatul Sivana; Putri Rahma Nurjannah; Ahc Fauzi; Asep Purwo Yudi Utomo; Ruhadi Ruhadi; Delsa Jelita Putri (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study aims to analyze news texts on the online news portal IDN Times. In addition, the study aims to identify various syntactic errors in the news texts on the portal, including non-standard sentence structures, the use of loanwords, ambiguous sentences, inappropriate diction, and low word efficiency, thereby providing an overview of the language quality and presentation of information in the online media. This research employs a qualitative descriptive approach, with a syntactic framework as the theoretical foundation. The researcher obtained data by reading several relevant references and recording information that could be used as data. Therefore, the reading and note-taking technique was used in this study. The data in this study consisted of news texts from the online news portal IDN Times, edition 2025. The data analysis method employed is the distributional method. The researcher analyzed the texts by identifying sentences that did not conform to syntactic rules and assessed the suitability of the texts as proper and accurate news texts. The results revealed various syntactic errors, including errors in sentence structure, diction, punctuation, sentence effectiveness, loanword usage, and conjunction usage. How ever, the findings indicate that although some syntactic errors were found, the news texts on the portal generally have a relatively good and coherent structure. Therefore, the texts can provide valuable insights into language use in the context of online media and serve as sources of information for studying language quality and effective communication in digital news writing.